(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
The purpose of this study is to analyze the human resource management as it is one of the areas most affected by the changes occurring in the modern world and to relate the new production model for the twenty-first century. It is a documental research. This was an evaluation of these eras in the twentieth century characterized by three distinct eras. The classical era of industrialization, which imposed a hierarchical, functional, where the specialization of the workers was the most important. Followed by the neoclassical era of industrialization characterized by a double hybrid design matrix organizational structure. It was the twenty-first century information age, organizations are moving towards globalization, people, knowledge, technology and results. The changes are predominantly violent and the importance of human and intellectual capital. Comes a new production model which emphasizes the self-directed work teams, it looks for repetitive tasks are performed by each worker machines and represent a source of value creation and strategic business unit. This is the initiative and motivate employee behavior, far more qualified. It has a humanization of the process, since each worker controls his own work because it has the necessary skills to do so. All workers are subject, and not at a voltage of productivity, but a creative tension.